The A-test: Assessment of functional recovery during early rehabilitation of patients in an orthopedic ward - content, criterion and construct validity - Vukomanović Aleksandra; Đurović Aleksandar; Popović Zoran; Pejović Vesna (Vojnosanitetski Pregled)
Background/Aim. The A-test was designed for assessment of functional recovery during early rehabilitation of patients in an orthopedic ward. This performance-based test consists of 10 items for assessing basic activities by a six level ordinal scale (0-5). Total scores can range from 0 to 50, i.e. from inability to perform any activity despite the help of therapists to complete independence and safety in performing all activities. The aim of this study was to examine the A-test validity. Methods. This prospective study was conducted in an orthopedic ward and included 120 patients [60 patients with hip osteoarthritis that underwent arthroplasty and 60 surgically treated patients with hip fracture (HF)] during early inpatient rehabilitation (1st-5th day). Validity was examined through 3 aspects: content validity - floor and ceiling effect, range, skewness; criterion validity - concurrent validity [correlation with the University of Iowa Level of Assistance Scale (ILAS) for patients with hip osteoarthritis, and with the Cumulated Ambulation Score (CAS) for patients with HF, Spearman rank correlation] and predictive validity [the New Mobility Score (NMS) 4 weeks after surgery, Mann-Whitney U test]; construct validity - 4 hypotheses: 1) on the fifth day of rehabilitation in patients underwent arthroplasty due to hip osteoarthritis, the A-test results will strongly correlate with those of ILAS, while the correlation with the Harris hip score will be less strong; 2) in patients with HF, the A-test results will be significantly better in those with allowed weight bearing as compared to patients whom weight bearing is not allowed while walking; 3) results of the A-test will be significantly better in patients with hip osetoarthritis than in those with HF; 4) the A-test results will be significantly better in patients younger than 65 years than in those aged 65 years and older. Results. The obtained results were: low floor (1%) and ceiling (2%) effect, range 0-50, skewness 0.57, strong correlation with ILAS for the patients with hip osteoarthritis (r = -0.97, p = 0.000) and with CAS for the patients with hip fracture (r = 0.91, p = 0.000) The patients with the A-test score 35 and more on the fifth day of rehabilitation (n = 46, Md = 4) had significantly higher NMS rank 4 weeks after surgery than the patients with the A-test score less than 35 (n = 59, Md = 2), (U = 379, z = -6.47, p = 0.000, r = 0.63). All 4 hypotheses were confirmed. Conclusion. The A-test is simple and valid instrument for everyday evaluation of pace and degree of functional recovery during early rehabilitation of patients surgically treated in an orthopedic ward.